A Hybrid RF/FSO Transmission System Based on a Shared Transmitter - Qinyi Zhang; Jianjun Yu; Jianyu Long; Chen Wang; Jiali Chen; Xin Lu (Sensors)
In this work, we propose a novel design of a hybrid transmission integrated system for radio frequency (RF) and free-space optical (FSO) communications, in which the RF and FSO links are able to share the transmitter and the transmission link. In this system, the RF link can usually be considered as a complement to the FSO link, and the hybridization of the two transmissions allows the system to adapt to a variety of complex environments while maintaining a high rate of transmission, improves system stability, and greatly reduces system complexity through the design of a shared transmitter. An experimental demonstration of the system has been carried out, and the results show that the hybrid RF/FSO system supports 50 Gbit/s transmission, satisfying the 20% soft-decision forward error correction (SD-FEC) threshold of 2.4 × 10−2. Additionally, for the FSO link, the system supports 100 GBaud QPSK and 32 GBaud 16QAM transmissions individually. The proposed structure combines the advantages of RF and FSO, providing a foundation for future high-speed, broadband, all-environment communication.